KORELASI STATUS GIZI DENGAN PERKEMBANGAN BALITA DI POSYANDU - Febrianti, Nuristha; Suyati, Suyati; Maryana, Nana; Sari Pribadi, Puspita; Anggraini, Vina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
Data on nutritional problems that are a factor in developmental delays at the Healthy Child Posyandu in Koto Mesjid Village include 0.024% malnutrition, 0.032% undernutrition, 0.080% overnutrition, 0% very short nutrition and 0% short nutrition, 0% very thin nutrition and 0% thin nutrition and 0.016% fat nutrition. The purpose of the study was to determine the correlation of nutritional status with the development of toddlers in healthy children's posyandu in Koto Mesjid Village. This study is an observational analytic quantitative study with a cross sectional design. The research location was in Koto Mesjid Village in 2023. The sample in this study amounted to 95 people. The sample is mothers who have toddlers in the village of Koto Mesjid. The sampling technique was purposive sampling. Data collection techniques using a research questionnaire. Data analysis was performed univariate and bivariate using the SPSS program. The results showed there was a relationship between nutritional status and the development of toddlers with a p value of 0.039. It is recommended that families should pay more attention to nutritional intake, so that children can grow and develop well in health.Keywords: Toddlers, Malnutrition, Nutritional Status.